PRELIMINARY STUDY OF THE ANTIMICROBIAL EFFECT OF A CLOVE ESSENTIAL OIL-BASED DISINFECTANT ON STAPHYLOCOCCUS COAGULASA POSITIVE AGENT OF BOVINE MASTITIS - Pulido Peñaloza, Luz Marina
Bovine mastitis is a disease that reduces milk production worldwide. There are several causes, such as those of bacterial origin, mainly Staphylococcus coagulasa positive. Antibiotic treatment is the option and disinfection of the tidying areas is the prevention tool. The use of natural substances with antimicrobial characteristics has been incorporated into disinfection processes to minimize the toxicity of chemical products. The objective of the study was to evaluate the effectiveness of disinfectant based on clove essential oil on S. coagulasa positive, the cause of bovine mastitis. The study was experimental and was carried out in the microbiology laboratory of SENA-CEDAGRO; in triplicate, extractions of clove essential oil were developed by hydrodesorption. From these, three solutions of different concentrations were prepared: 50 mg / ml (T3), 100 mg / ml (T2) and 150 mg / ml (T1). The in vitro bactericidal action was evaluated by agar diffusion against Escherichia coli, S. aureus and Salmonella tiphymurium strains on filter paper discs. Inhibition halos of larger diameter were observed for S. aureus and E. coli than for S. tiphymurium at the concentration of 150 mg / ml. A 15% essential oil disinfectant was prepared and used on surfaces in the sorting area where cattle have direct contact with equipment on the El Caney farm, as well as the commonly used sodium hypochlorite at 100 ppm. Swabs were taken before and after disinfection, showing a decrease in the growth of S. coagulasa positive in both cases. Statistically, there were significant differences between the microbiological results of the two stages tested: in the bactericidal action of clove essential oil on S. aureus, E. coli and S. tiphymurium microorganisms and in the microbiological analyses in which clove and sodium hypochlorite solutions were used for disinfection.